Targeting ubiquitin signaling for cancer immunotherapy - Zhou, Xiaofei; Sun, Shao-Cong (Signal transduction and targeted therapy, 2021)
Cancer immunotherapy has become an attractive approach of cancer treatment with tremendous success in treating various advanced malignancies. The development and clinical application of immune checkpoint inhibitors represent one of the most extraordinary accomplishments in cancer immunotherapy. In addition, considerable progress is being made in understanding the mechanism of antitumor immunity and characterizing novel targets for developing additional therapeutic approaches. One active area of investigation is protein ubiquitination, a post-translational mechanism of protein modification that regulates the function of diverse immune cells in antitumor immunity. Accumulating studies suggest that E3 ubiquitin ligases and deubiquitinases form a family of potential targets to be exploited for enhancing antitumor immunity in cancer immunotherapy.